HUBUNGAN PROFITABILITAS DAN DIVIDEN TUNAI DENGAN ICECUKUPAN KAS DAN LIKUIDITAS SEBAGAI MODERATING VARIABLE - Megawati Olctorina; Michell Suharti (Media Riset Akuntansi, Auditing & Informasi, 2007)
The objective of this research is to determine the relationship between profitability and the amount of cash dividend policy. However this research examines the influences of cash adequate and liquidity (current ratio)toward the relationship between profitability and cash dividend policy. We call the influence as moderating variables. In general, investors have primarily objective that is to increase their wealth by return as dividend or capital gain. On the other hand, the companyexpects continuous growth and its going concern, also increase its stockholder's wealth. Factor that predicted influencing dividend distribution amount in this research are focused on profitability. Thus, profitabiNy influences cash dividend policy in a company. However cash dividend should be paid only when a company has adequate cash and good liquidity ratio. This research examines financial statement of several companies are listed at Jakarta Stock Exchange for period ended December 31, 2000 until December 31, 2003. Data is collected from Jakarta Stock Exchange and Indonesia Capital Market Directory 2004. This research uses statistical software TViews version 4,1 ''. The result is cash adequate and liquidity moderate relationship between return on investment and cash dividen policy. On the other hand, return on equity has not significant relationship with cash dividend PolicyKeyword : profitability, cash dividend, cash adequate, liquidity